PROSES PERENCANAAN DAN PENGANGGARAN KEUANGAN DESA (Studi Di Desa-Desa Kecamatan Giri Mulya Kabupaten Bengkulu Utara) - Baihaqi Baihaqi; Ratih Pelita Sari; Dri Asmawanti S (Jurnal Akuntansi, 2017)
This research is a descriptive qualitative research that aims to explain the condition of planning process and budgeting of village finances in the villages of Giri Mulya Sub-district, North Bengkulu Regency. The informants of this research are the village head, village secretary, head of the village consultative body, the empowerment of the village community of Giri Mulya sub-district, and representatives from the community. Data were collected through observation process, in-depth interview and documentation. The results of this study indicate that village planning and village financial budgeting have been outlined in accordance with the prevailing regulations. In terms of timeliness, in determining the work plan of the local government and budget of village income and expenditure, there was a delay due to the lack of human resources quality and the problem of regulatory delays from the district that reached the village head.Keywords : planning and budgeting of village finances, Human Resources, regulatory